Effect audit committee financial expertise toward assets misappropriations / Nurul Aida Abd Ghani - Abd Ghani, Nurul Aida (2011)
This descriptive study is done to the application of an Effect of Audit Committee Financial Expertise and Assets Misappropriation. The study was carried out with the purpose to identify the audit committee financial expertise, audit committee accounting expertise, audit committee non-accounting expertise and independent member in financial expertise. This study was used the secondary data to get the data statistics about the misappropriated assets cases and the financial expertise. Then response was evaluated by using Statistical Package for Social Science (SPSS) Version 16.0. The research was analyzed descriptively and tabled as Cross-tabulation, Multiplier Linear Regression, Correlation Coefficient and Chi-Square. The finding of this study shows that the misappropriated of assets is influenced by the audit committee financial expertise, audit committee accounting expertise, audit committee non-accounting expertise and independent member in financial expertise. There are negative relationship between dependent variable and independent variables. Which mean that the audit committee financial expertise, audit committee accounting expertise, audit committee non-accounting expertise and independent member in financial expertise (IV) increase, the Misappropriation of assets (DV) will decreased. Finally there are some suggestions forwarded to reduces the misappropriated of assets cases by give the knowledge to the workers about the white-collar crime law